The Extent of Usage of Mobile Phones and the Academic Performance as well as Moral Development of the Undergraduate Students: An Analysis - Javaid, Muhammad Arshad; Zahra, Annam; Raheem, Muhammad Arslan (Annals of Human and Social Sciences, 2024)
The main objective of the study was to find out the effect of the extent of mobile phone usage on the academic performance and moral development of undergraduate students. The study was delimited to only female students studying at University of Education Lahore, D. G. Khan Campus.199 female students were selected as a sample through stratified random sampling technique. A check list and two questionnaires were developed to collect the data from the sample of the study. The check list was used to classify the students’ groups as per their extent of the usage of mobile phones. The questionnaire (Q1)and (Q2) were developed to find out the level of academic performance and the moral development of the desired sample. It was concluded that the increasing extent of usage of mobile phones affect the students academic performance as well as moral development. It was recommended that in universities, particularly; in the class rooms, during teaching learning process, usage of mobile phones may be prohibited.